Pelatihan Pembuatan Pakan Ternak Sapi Fermentasi Berbasis Limbah Pertanian - Armayani Muhardi (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2023)
The service activity with the title Training on Making Fermented Cattle Feed Based on Agricultural Waste aims to increase the competence of breeders in processing feed ingredients to become of higher quality and produce feed based on agricultural waste as an alternative to forage substitute feed. This activity was carried out through several stages, namely: Introduction of feed ingredients (Aspects of scientific theory), Training on Agricultural Waste-Based Fermentation Processing, and Harvesting-Giving Livestock. The method applied is Participatory Rural Appraisal (PRA). This method provides an opportunity for partners to be able to observe, study, share, improve and analyze knowledge about the conditions of farmers in processing quality local raw materials. PRA is substantially a method to find out the potential and problems of partners and provide solutions to solve various problems found. Based on the results of the activity, it was found that the potential for agricultural waste that could be used as animal feed at partner locations included: rice straw, peanut straw, and corn buns. These three types in principle can complement each other's nutritional needs, especially if they are used as substitute feed. The conclusion that can be drawn from this activity is that the utilization of the three identified types of waste can be used as cattle feed which can be processed through mechanical (physical) and biological treatment through fermentation techniques. The evaluation results obtained are in a position at 90.57.